PENERAPAN GROWTH MINDSET DALAM PEMBELAJARAN MENDALAM UNTUK MENINGKATKAN PERKEMBANGAN MURID PPKn PADA MURID KELAS VII DI SMPN 23 MALANG - Nur Wahyuningsih Ramadhani; Siti Halimatus Sakdiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research (CAR) aimed to improve student development in Civics Education (PPKn) by applying a Growth Mindset approach within a deep learning framework for seventh-grade students at SMPN 23 Malang. The study was motivated by low pre-cycle achievement in class VII-3, where 73.33% of students (22 of 30) had not met the minimum mastery criterion (KKM) of 75, with a class average of 63.4. The research used two cycles, each with a pretest, four sessions, and a posttest, involving 30 students in the 2025/2026 academic year. Results showed progressive improvement: the class average rose to 73.6 (60% mastery) in Cycle I and to 83.7 (86.67% mastery) in Cycle II, surpassing the 80% success indicator. Growth Mindset behaviors also rose from 22% to 81% of students. These findings show that integrating Growth Mindset with deep learning strategies such as collaborative inquiry, reflective journaling, and Socratic questioning meaningfully strengthens both academic achievement and intrinsic motivation in PPKn.